The Effect of Red Ginger (Zingiber officinale var. rubrum) Extract Administration on the Number of Spermatogenic Cells and Leydig Cells in White Rats (Rattus norvegicus) Exposed to Monosodium Glutamate - Ahmad Fahrisa Sidharta; Kadek Rachmawati; Rimayanti; Budi Utomo; Nove Hidajati; Kuncoro Puguh Santoso; Rahmi Sugihartuti; Rochmah Kurnijasanti (Journal of Basic Medical Veterinary, 2026)
The purpose of this study was to examine the effect of red ginger extract (Zingiber officinale var. rubrum) on the number of spermatogenic cells and Leydig cells in white rats (Rattus norvegicus) exposed to monosodium glutamate (MSG). This study used 25 male white rats divided into five treatment groups. The K− group received 1% CMC-Na, the K+ group received MSG at a dose of 5 g/kg body weight (BW), and the P1 to P3 groups received MSG at 5 g/kg BW along with red ginger extract at doses of 50 mg/kg BW, 100 mg/kg BW, and 200 mg/kg BW, respectively, for 42 days. The rats’ testes were collected, processed into histopathological preparations, and observed under a microscope at 400× magnification. Data were analyzed using one-way ANOVA followed by Duncan’s test. The results showed significant differences (p < 0.05) in the number of spermatogenic cells and Leydig cells among the K−, K+, P1, and P2 groups, but no significant differences (p > 0.05) were observed between the K− group (57.60ᵈ ± 1.490 and 14.92ᵈ ± 1.487) and the P3 group (57.20ᵈ ± 1.208 and 14.84ᵈ ± 1.459). The optimal dose of red ginger extract was 200 mg/kg BW (P3). In conclusion, administration of red ginger extract can maintain the number of spermatogenic cells and Leydig cells in white rats (Rattus norvegicus) exposed to MSG.